PROSES MANUFAKTUR TURBIN ANGIN SUMBU VERTIKAL TIPE DARRIEUS - Rian Effendi; Rudi Siswanto (JTAM ROTARY, 2019)
Wind turbine is one of the tools yamg work to take advantage of wind allergy. Wind turbines based on the type of rotor there are two types of Darrieus wind turbines and Savonius wind turbines. In the manufacturing process using a type of wind turbine type Darrieus. The darrieus turbine is a wind turbine that utilizes the lift style on the rotor blade. This turbine requires initial energy to spin. The formulation of the problem in making this wind turbine is How does the manufacturing process of vertical turbine type darrieus wind turbine and How much is the cost budget on the manufacturing process of the darrieus type verical wind turbine. The components of the wind turbine are the foot frame, bearing bearings, bearings, shafts, disks, blade arms, blades, transmission pulleys and belts-v, while the tools and machinery used in the manufacturing process are electric welding tools, electric grinding wheels, , hand drilling machine, sitting drilling machine, cut lever, riverter pliers, acetylene welding and lathe. Keywords: Wind Turbine, Turbine Components, Tools and MachinesApple, JM. Tata Letak Pabrik dan Pemindahan Bahan. Bandung : Penerbit ITB, Terj. Nurhayati Mardiono.,1990.Maheswari Hesti,Achmad Dany Firdauzy.2015. “Evaluasi Tata Letak Fasilitas Produksi Untuk Meningkatkan Efisiensi Kerja Pada Pt. Nusa Multilaksana. Fakultas Ekonomi”. Jakarta:Universitas Mercu Buana.Susetyo Joko dkk.2010. “Perancangan Ulang Tata Letak Fasilitas Produksi Dengan Pendekatan Group Technology Dan Algoritma Blocplan  Untuk Meminimasi Ongkos  Material Handling”. yogyakarta:AKPRIND.Nova St Meirizha. 2014. “Perancangan Ulang Tata Letak Fasilitas Pada Hanggar Pemeliharaan Pesawat Hawk 100/200  Di Pangkalan Udara Roesmin Nurjadin”. Riau: Program Studi Teknik Industri, Fakultas Teknik,Universitas Muhammadiyah.Wignjosoebroto, sritomo. Tata letak pabrik dan pemindahan bahan. Surabaya: penerbit guna widya., 1996.